2008
DOI: 10.1093/hmg/ddn065
|View full text |Cite
|
Sign up to set email alerts
|

Multiple layers of molecular controls modulate self-renewal and neuronal lineage specification of embryonic stem cells

Abstract: Elucidating the molecular changes that arise during neural differentiation and fate specification is crucial for building accurate in vitro models of neurodegenerative diseases using human embryonic stem cells (hESCs). Here we review the importance of hESCs and derived progenitors in treating and modeling neurological diseases, and summarize the current efforts for the differentiation of hESCs into neural progenitors and defined neurons. We recapitulate the recent findings and discuss open questions on aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…In addition, some enhancers are also marked by RNA polymerase II and eRNA (enhancer RNA) transcripts ( 15 , 16 ). Embryonic stem (ES) cell differentiation has provided insight into the chromatin structure at the ‘ground’ state ( 17 , 18 ) as well as information on transitions during the differentiation of specific cell types such as neuronal progenitors ( 19 ). It has been shown that many developmental regulatory genes posses a ‘bivalent domain’ structure comprised of a broad H3K27me3 and a narrow H3K4me3 region at their promoters ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some enhancers are also marked by RNA polymerase II and eRNA (enhancer RNA) transcripts ( 15 , 16 ). Embryonic stem (ES) cell differentiation has provided insight into the chromatin structure at the ‘ground’ state ( 17 , 18 ) as well as information on transitions during the differentiation of specific cell types such as neuronal progenitors ( 19 ). It has been shown that many developmental regulatory genes posses a ‘bivalent domain’ structure comprised of a broad H3K27me3 and a narrow H3K4me3 region at their promoters ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of microRNA–mediated repression in different mRNA isoforms has been successfully used to associate MRE sites with functions in many studies, such as the prediction of target mRNAs [37-41], the influence of intron retention on human mRNA [42], cellular proliferation and differentiation [12,43], and cancer [44]. The effect of fine-tuning at the splicing level would be negligible if the associated MREs are not highly repressive.…”
Section: Resultsmentioning
confidence: 99%
“…Within these heterogeneous cell populations, neural rosettes are formed from which neural cells may be separated from other cell types. 39, 40 Newer alternative strategies for feeder-free, directed differentiation to NSCs utilizing chemical inhibitors and purified protein activators of specific signaling pathways important in fate determination have also been developed. 41, 42, 43 Further differentiation utilizing more specific cocktails of small molecules and purified protein for enrichment of neuronal subtypes such as dopaminergic populations has been applied to hiPSC studies in Parkinson's disease.…”
Section: Human-induced Pluripotent Stem Cells As a Tool To Address Somentioning
confidence: 99%